AN EFFICIENCY REPORTING SYSTEM FOR ORGANISATIONAL SUSTAINABILITY BASED ON WORK STUDY TECHNIQUES - Sookdeo, Barnes (The South African Journal of Industrial Engineering, 2016)
This article aims to demonstrate that work study techniques must be used to determine standard times for operations and to develop efficiency reporting systems to sustain organisations. Many organisations do not measure their efficiencies and do not have reporting systems. This article presents an efficiency reporting system designed and based on work study techniques that can be used to measure performance. The empirical results of the research instrument supported the need for the system. The existence of a dedicated efficiency reporting system ensures that employee performance and outputs in line with set targets are measured and sustained.